De Jong op rondvaart in Amsterdam in de jaren 60. Foto van originele foto uit collectie H.C. Bruyel Bruinewoud
De Jong op rondvaart in Amsterdam in de jaren 60. Foto van originele foto uit collectie H.C. Bruyel Bruinewoud.